Non-clinical toxicological evaluation of the ethanolic extract from Zornia brasiliensis Vogel (Fabaceae) - Tatianne Batista, Renata Abrantes, Aline Xavier, João Carlos Pita, Monalisa Brito, Adriano Alves, Anne Dayse, Yuri Nascimento, Sócrates Santos, Josean Tavares,, Marcelo Silva,, Marianna Sobral, (Journal of Applied Pharmaceutical Science, 2021)
Zornia brasiliensis Vogel, Fabaceae, is used to treat venereal diseases and as diuretic in Brazilian northeast folk medicine. Herein, the toxicity profile of ethanolic extract from Z. brasiliensis aerial parts (ZBEE) was evaluated. Hemolysis assay was used to evaluate the in vitro toxicity, where as in vivo acute and repeated-dose (28 days) toxicity tests were performed on adult Swiss albino mice. Micronucleus test was used to evaluate genotoxicity. The concentration of ZBEE that produced 50% hemolysis (HC50) was 1,954 μg/ml, indicating low cytotoxicity. In acute toxicity assay, no deaths or behavioural changes in mice treated with 2,000 mg/kg ZBEE were recorded. Regarding the repeated-dose evaluation, after 28 days of treatment with ZBEE (250, 500, and 1,000 mg/kg, oral gavage), weak toxicity signs on biochemical, haematological, and neurological parameters were observed, especially for the highest dose tested. ZBEE (2,000 mg/kg) did not induce an increase in micronucleated erythrocytes number, suggesting no genotoxicity. In summary, ZBEE showed low nonclinical toxicity. These data support its safe use in the folk medicine and further studies to characterize the pharmacological activities of this medicinal plant.
Keywords: Acute toxicity, repeated-dose toxicity, genotoxicity. Zornia.